2017
DOI: 10.1177/0363546517706964
|View full text |Cite
|
Sign up to set email alerts
|

Elbow Injuries in Professional Baseball: Epidemiological Findings From the Major League Baseball Injury Surveillance System

Abstract: Elbow injuries are a considerable source of disability in professional baseball players. Pitchers are most likely to incur these injuries, are most likely to require surgery, and have the highest mean number of days missed when treated nonsurgically. The most common injuries involve the medial elbow, with ligament injuries most often requiring surgery. This study represents the only investigation to date using a comprehensive injury surveillance system to examine elbow injuries in professional baseball players… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
95
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 29 publications
0
95
0
Order By: Relevance
“…To date, 25% of Major League pitchers and 15% of Minor League pitchers have had Tommy John surgery at some point in their career 5. In a recent comprehensive epidemiological study, Ciccotti et al 18 found that 33%–43% of elbow injuries in US professional baseball require surgery, with UCL reconstruction being the most frequently performed procedure. Although no increase in the frequency of elbow injuries was observed over recent seasons in this population, Erickson et al reported a significant increase in UCL reconstructions performed from 2000 to 2012 5 18 54 55…”
Section: Considerationmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, 25% of Major League pitchers and 15% of Minor League pitchers have had Tommy John surgery at some point in their career 5. In a recent comprehensive epidemiological study, Ciccotti et al 18 found that 33%–43% of elbow injuries in US professional baseball require surgery, with UCL reconstruction being the most frequently performed procedure. Although no increase in the frequency of elbow injuries was observed over recent seasons in this population, Erickson et al reported a significant increase in UCL reconstructions performed from 2000 to 2012 5 18 54 55…”
Section: Considerationmentioning
confidence: 99%
“…A recent epidemiological study by Ciccotti et al 18 indicated that elbow injuries are the fourth most prevalent type of injury in the US professional baseball population (7.8% in Major League Baseball and 9.8% in Minor League Baseball), accounting for the highest number of days missed of all musculoskeletal injuries. In this population, 39%–53% of elbow ligament injuries require surgery, predominantly in pitchers and primarily involving the UCL 18.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overhead throwing athlete must harness a complex transfer of energy which utilizes the entire kinetic chain, requiring muscle activation and sequencing through the lower extremities to the core and trunk to propagate the transfer of power to the upper extremity [1,2]. With repetitive throwing, this transfer of power and subsequent dynamic overload to the upper extremity may cause injury in baseball players, often presenting with shoulder and elbow injuries [3,4]. More recent focus on upstream kinetic chain mechanics has suggested that limited mobility, strength, or conditioning at any point within the kinetic chain can impact the athlete's throwing performance [5•, 6-9].…”
Section: Introductionmentioning
confidence: 99%
“…Injuries seen in equestrian sports usually involve head and extremities and may require surgical treatment [2,3]. In the literature, injuries in those who are involved in professional sports are described in details, however data on injuries in those who are involved in riding are limited [2,[4][5][6][7]. Although it is a sport branch with high risk, epidemiological studies on injury patterns are rare [4].…”
Section: Introductionmentioning
confidence: 99%